Diagnostic pediatric ultrasound - Beek, Erik; Rijn, Rick R. van (Thieme, 2015)
Complete with advice for creating a child-friendly environment, examining infants and children, communicating with parents, and diagnosing complex cases, Diagnostic Pediatric Ultrasound makes a major contribution to the field. It will increase the know-ledge and skills of all pediatric and general radiologists, radiology residents, pediatricians, and other specialists who use ultrasound to care for this sensitive population